Supply Response of Chillies in Arid Districts of Western Rajasthan - Kalla, Jagdeesh C; Vyas, D L (Annals of Arid Zone, 2016)
District-wise secondary data for arid districts of western Rajasthan reporting more than 50U ha area under chillies (Jalore, Jodhpur, Nagaur and Pali) were used to study its supply responses. The response was stipulated to follow dynamic Nerlovian model. The results revealed that price signals play a key role in the decision making process on area allocation. Extension of irrigation facilities leading \0 higher yield would inevitably attract more area under chillies in arid region of western Rajasthan.